A study of nanorriutit—polar bear hunting dogs in Avanersuaq - Manumina Lund Jensen (Arctic Science)
Nanorriutit are specialized dogs integral to traditional nanoq (polar bear) hunting in Avanersuaq (Thule district, North Greenland). This practice, involving a deep relationship between the piniartoq (hunter), the nanoq, and the qimmeq (dog), is a crucial aspect of Inughuit cultural heritage in the region. However, the hunting culture associated with nanorriutit faces significant challenges due to the contemporary lifestyle, urbanization and impacts of climate change, which are deteriorating the traditional hunting grounds. This study aims to examine the evolving role of nanorriutit in polar bear hunting practices and the broader cultural context of Avanersuaq. Utilizing a qualitative approach, data were collected through fourteen semi-structured interviews with thirteen knowledge holders from the settlement of Savissivik and the town of Qaanaaq, conducted in Inuktun and kalaallisut. The findings illustrate both the enduring significance of nanorriutit, and the adaptations required in response to changing environmental conditions. This research contributes to the understanding of how the contemporary lifestyles and climate change is influencing Inughuit hunting practices and emphasizes the need to preserve this valuable cultural tradition amidst a rapidly transforming Arctic urbanization and environment.